Design, construction and testing of an apricot tractor-trailed harvester - Torregrosa, A.=700 1 Chaparro, O.; Martin, B.; Ortiz, C.; Bernard, J.J.; Orti, E.; Gil, J.; Perez, M.
(Es, En)
Ilus., 13 ref.
Keywords: DISEÑO; COSECHADORAS; EQUIPO DE RECOLECCION DE FRUTAS; PRUNUS ARMENIACA; ESPAÑA; SPANISH JOURNAL OF AGRICULTURAL RESEARCH